Cardiac Lesions in 30 Dogs Naturally Infected With Leishmania infantum chagasi - Rosa, F. A. [UNESP]; Leite, J. H. A. C. [UNESP]; Braga, E. T. [UNESP]; Moreira, P. R. R. [UNESP]; Baltazar, F. H. [UNESP]; Biondo, A. W.; Padua, P. P. M. [UNESP]; Vasconcelos, R. O. [UNESP]; Camacho, A. A. [UNESP]; Ferreira, W. L. [UNESP]; Machado, G. F. [UNESP]; Marcondes, M. [UNESP] (Sage Publications Inc, 2014)
The hearts of 30 dogs naturally infected with Leishmania infantum chagasi were evaluated histologically and immunohistochemically. Myocardial lesions were detected in all dogs, including lymphoplasmacytic myocarditis (27/30), myonecrosis (24/30), increased interstitial collagen (22/30), lepromatous-type granulomatous myocarditis (7/30), fibrinoid vascular change (3/30), and vasculitis (1/30). The parasite was detected in the hearts of 20 of 30 dogs. The number of parasitized cells correlated with the intensity of the inflammation and with the number of granulomas. The results indicate that cardiac lesions are prevalent in dogs with naturally occurring leishmaniasis even in the absence of clinical signs of cardiac disease.
Keywords: Dog; myocarditis; Immunohistochemistry; Leishmaniasis